2022
DOI: 10.1002/arch.21965
|View full text |Cite
|
Sign up to set email alerts
|

Identification of entomopathogenic fungus Metarhizium rileyi infested in fall armyworm in the cornfield of Korea, and evaluation of its virulence

Abstract: The fall armyworm (FAW) Spodoptera frugiperda is an important invasive pest in Africa and Asia. It is a polyphagous pest with at least 353 recorded host plant species, including corn. Chemical control of this pest is unsuccessful because of a developed resistance and harmful effects on the environment. Entomopathogenic fungi are potential biological control agents for FAW. In this study, the native strain of Metarhizium rileyi (KNU‐Ye‐1), collected from a cornfield at Yeongcheon, Korea, was identified by morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The evolutionary relatedness of isolated entomopathogenic fungi was determined using neighbor‐joining trees. Acharya et al [38]. isolated the entomopathogenic fungus M. rileyi from fall armyworms discovered in a cornfield in Korea and observed similar characteristics.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The evolutionary relatedness of isolated entomopathogenic fungi was determined using neighbor‐joining trees. Acharya et al [38]. isolated the entomopathogenic fungus M. rileyi from fall armyworms discovered in a cornfield in Korea and observed similar characteristics.…”
Section: Discussionmentioning
confidence: 93%
“…The morphological and molecular levels of these fungi were found to be comparable to those observed in our current study. Furthermore, the virulence of the fungus was tested on S. frugiperda larvae, resulting in an 89% mortality rate within 7 days [38].…”
Section: Discussionmentioning
confidence: 99%
“…Collecting a large number of corpse samples may help to elucidate the mechanism driving the prevalence of M. anisopliae in insects [ 50 ]. For example, Isaria javanica (Bally) Samson & Hywel-Jones and I. fumosorosea Wize are common fungi that are widely used for aphid and whitefly control and other fungal insecticides, making them readily isolated from these hosts [ 51 , 52 ]. In addition, the prevalence, distribution, and fungal infection of insect fungal pathogens are affected by weather parameters, such as temperature, rainfall, and humidity [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the dipping method was used to determine the virulence of fungi with 1 × 10 7 /mL conidia against insect larvae. It is reported that the fourth-instar larvae of S. frugiperda were inoculated by spraying with M. rileyi KNU-Ye-1 conidial suspension (1 × 10 7 /mL), and the mortality was 89% after 7 days [ 52 ]. The reason for the difference may be that the method of virulence determination and the concentration of the fungal spore suspension are different.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, more than 1,000 species of EPF have been reported, including commercially applied Metarhizium anisopliae , Beauveria bassiana , Isaria fumosorosea, and Metarhizium rileyi ( Kim Jae et al, 2013 ; Grijalba Erika et al, 2018 ; Jiang et al, 2019 ; Malinga Lawrence and Mark, 2021 ; Wang et al, 2021 ; Acharya et al, 2022 ; Faria et al, 2022 ; Im et al, 2022 ), as well as literature reported Paecilomyces var iotii , Hirsutella citriformis , and Akanthomyces lecanii ( Gandarilla-Pacheco et al, 2013 ; Cortez-Madrigal et al, 2014 ; Hussain et al, 2018 ; Naeem et al, 2020 ). However, the resources of EPF are insufficient due to their host specificity, which could affect their commercial production and application ( Wichadakul et al, 2015 ; Zhang et al, 2020 ; Islam et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%